Simultaneous Prostate Target Biopsy Integrated With Radical Prostatectomy: A Pilot Study Omitting Preoperative Systematic Biopsy - Park, Tae Young; Hwang, Jae Young; Yun, Seong Woo; Hyun, Chang Wan; Yoon, Sung Goo; Kim, Seung Bin; Noh, Tae Il; Shim, Ji Sung; Park, Min Goo; Kang, Seok Ho; Kang, Sung Gu (Journal of Urologic Oncology, 2024)
Purpose: This study evaluates the viability of a new method that employs transperineal targeted biopsy with frozen section analysis immediately followed by robot-assisted radical prostatectomy (RARP), bypassing the traditional systematic biopsy deemed essential by current guidelines.Materials and Methods: Patient selection was based on the following inclusion criteria: those who underwent magnetic resonance imaging (MRI)-ultrasound fusion-targeted biopsy with frozen section analysis and concurrent RARP. Eligibility also required features indicative of Prostate Imaging-Reporting and Data System (PI-RADS) 5 lesion on multiparametric MRI, along with one of these additional criteria: (1) MRI evidence suggesting extracapsular extension (ECE) with a prostate-specific antigen (PSA) level >10 ng/mL, or (2) a PSA level > 20 ng/mL.Results: Twelve patients were enrolled in this study according to inclusion criteria. The median age (interquartile range) was 73.5 (69.5–75.3) years and PSA was 22.9 (17.0–29.9) ng/mL. Three patients had PI-RADS 5 lesions, and 9 had PI-RADS 5 lesions with findings of ECE. In all cases, the diagnosis based on frozen sections confirmed adenocarcinoma. Following confirmation, each patient underwent immediate RARP. According to the final pathology report, 2 patients had International Society of Urological Pathology (ISUP) grade 2 disease, 7 patients had ISUP grade 3, 1 had ISUP grade 4, and 2 had ISUP grade 5 disease. Four patients had stage pT2 disease, 3 had stage pT3a, and 5 had stage pT3b. The median immediate reporting time of the target biopsy frozen section was 20 (19.3–24.5) minutes. No perioperative complications related to target biopsy were observed.Conclusion: For patients with a strong suspicion of prostate cancer and a PI-RADS 5 lesion, integrating simultaneous prostate frozen target biopsy with radical prostatectomy may offer a feasible treatment alternative, obviating the necessity for a preoperative systematic biopsy.